Photoinduced polycondensation processes in molybdenum and vanadium mixed oxide thin films: towards novel photolithographic material - Sviridova, Tatsiana V.; Logvinovich, Aliaksandr S.; Odzaev, Vladimir B.; Sviridov, Dmitry V. (Journal of the Belarusian State University. Chemistry, 2023)
Investigation of the mechanism of UV-induced polycondensation in the oxoacid-derived mixed oxide V2O5 : MoO3 (molar ratio of oxides was 3 : 2) films employing fractal analysis of AFM images has evidenced that solid-state polymerisation process via 3D-mechanism resulting in the increased roughness of the microrelief of the film accompanied, however, with decrease of the fractal dimension. The polycondensation is accompanied with ordering yielding nuclei agglomerates built of nanometer-sized faceted pseudocrystals which become visible after development in the acid solution. These alignment effects, that result in the recovery of the photoresist film microrelief and the increase of the fractal dimension to the initial value ensures the dimension stability and sharp edges in the case of patterns generated with MoO3 : V2O5 photoresist films.
Keywords: photopolymerisation; molybdenum and vanadium mixed oxide; photoresists